Pemberdayaan Pembibitan Kayu Manis di Kelurahan Jaya Kota Tidore Kepulauan - Asiah Salatalohy; Aisjah Rahmawati Ryadin; Firlawanti Lestari Baguna (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Tidore Islands City is one of the cinnamon producers in North Maluku Province. Several Kelurahans in this area have cinnamon potential, one of which is Kelurahan Jaya. This area is a producer of cinnamon which is quite famous and is often traded. However, farmers are less interested in cultivating cinnamon, one of the reasons is that the price is far below the other two commodities, namely cloves and nutmeg. It's just that production at the farm level decreased because the sale of this commodity did not match the exchange rate received. In addition, the lack of public knowledge about cultivation will have an impact on its sustainability in the future as well as the lack of exploitation and product diversification. This Community Service activity aims to provide knowledge to farmer groups about cinnamon nurseries. This activity was carried out by the method of discussion and giving lectures which were carried out between the lecturer team and representatives of the CAWADA farmer group in Jaya Village. Community service activities were carried out in Jaya Village, Tidore Islands City on 16-17 July 2022. The writing method used a descriptive approach. The results of the farming business analysis show that the price of cinnamon bark is quite low when compared to clove and nutmeg commodities. The profit obtained by clove commodities can reach Rp. 9,500,000 – 38,500,000, -. / tree. Meanwhile, the price of dried nutmeg flower / mace is 9 times or Rp. 250.000,-/kg. Cinnamon plant nurseries can be done in Tidore Islands City because the condition of this area has an ideal topography and altitude for cinnamon plants. Several types of vegetable crops such as chayote, eggplant and chili as well as local fruits can be planted together through the Agroforestry system with fence and alley cropping patterns. The nursery stage is carried out through land selection, preparation of seeds to planting.